Model-Model Pembelajaran yang Interaktif dan Menyenangkan untuk Pengajaran PPKN dalam Dekade Baru: Interactive and Enjoyable Learning Models for Civics Education Teaching in the New Decade - Sintia, Sintia (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The teaching of Pancasila and Civic Education (PPKN) becomes a crucial element in forming young generations that possess national character, social skills, and awareness of democratic values. In this new decade, teaching approaches are demanded to be more interactive, enjoyable, and relevant to students' needs. This research aims to identify and evaluate innovative learning models that can support PPKN teaching through the method of literature study. Learning models such as project-based learning, cooperative learning, and problem-based learning are analyzed in depth, especially in the context of increasing student engagement, learning motivation, and understanding of citizenship issues. The study results show that the use of interactive learning models not only makes the learning process more engaging but also provides space for students to think critically, collaborate, and understand the application of Pancasila values in daily life. On the other hand, enjoyable learning strategies contribute to the improvement of academic achievement while simultaneously strengthening students' social attitudes. This study recommends the implementation of these learning models in the PPKN curriculum to create meaningful learning experiences and shape student characters as responsible citizens.